Evaluation of Flood Pump Capacity in the Madiun City Area to Overcome Waterlogging in the Catchment Area of the City's Drainage Channel - Sri Teguh Sumaryanto; Mochamad Solikin; Purwanti Sri Pudyastuti (Green Publisher Indonesia, 2025)
Flooding has become an increasingly critical global challenge, with urban areas experiencing more frequent and severe flood events due to climate change and rapid urbanization. This research evaluates the capacity of flood pumps in Madiun City, Indonesia, to address waterlogging issues in urban drainage catchment areas. The objective of this study is to assess the adequacy of existing pump systems using hydrological analysis and determine the required pump capacity improvements for effective flood control. This research employed a quantitative descriptive method, utilizing primary data from field measurements and secondary data from relevant agencies. The study area encompasses eight pump houses in Madiun City with varying pump capacities. Hydrological analysis was conducted using rainfall data from 2011 to 2021, applying the Nakayasu Synthetic Unit Hydrograph method and Pearson III Log distribution for design rainfall calculation. Results indicate that existing drainage channels can accommodate flood discharge for return periods up to 25 years but require normalization for 50-, 100-, and 1000-year return periods. The Cassowary pump house analysis showed that the current pump capacity of 3 m³/s with a 4.23 m head is adequate for the 10-year return period. The research demonstrates that pump system effectiveness is crucial for flood control in low-lying urban areas. This study contributes to flood management literature by providing a systematic evaluation framework for urban pump systems and offers practical recommendations for municipal infrastructure planning.